2023
DOI: 10.1097/j.pain.0000000000002868
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability is not suitable as a surrogate marker for pain intensity in patients with chronic pain

Abstract: The search towards more objective outcome measurements and consequently surrogate markers for pain started decades ago; however, no generally accepted biomarker for pain has qualified yet. The goal is to explore the value of heart rate variability (HRV) as surrogate marker for pain intensity chronic pain setting. Pain intensity scores and HRV were collected in 366 patients with chronic pain, through a cross-sectional multicenter study. Pain intensity was measured with both the visual analogue scale and numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…62 The recent high-quality study demonstrated a similar lack of significant HRV findings with pain intensity. 63 Hence, our findings challenge the use of HRV measurements as an objective outcome measurement in future clinical trials related to CMP conditions, because there is only little association with the subjective core outcome measures of pain intensity, disability, and quality of life. 64 It is known that demographic factors, such as sex, age, and body mass index have major effects on HRV results.…”
Section: Discussionmentioning
confidence: 79%
“…62 The recent high-quality study demonstrated a similar lack of significant HRV findings with pain intensity. 63 Hence, our findings challenge the use of HRV measurements as an objective outcome measurement in future clinical trials related to CMP conditions, because there is only little association with the subjective core outcome measures of pain intensity, disability, and quality of life. 64 It is known that demographic factors, such as sex, age, and body mass index have major effects on HRV results.…”
Section: Discussionmentioning
confidence: 79%
“…Exclusion criteria included evidence of an active disruptive psychiatric disorder that may impact perception of pain (such as psychosis, anxiety disorders, major depression and substance or alcohol abuse) and patients with one or more co-existing conditions known to affect heart rate variability analysis. The detailed methodology and results of the INTERVAL study are published elsewhere [15]. To summarise, all patients were asked to complete four NRS scales and four VAS scales, provided electronically through Qualtrics XM (Qualtrics International Inc., Seattle, WA, USA) on a tablet.…”
Section: Methodsmentioning
confidence: 99%
“…This study was approved by the central ethics committee of Universitair Ziekenhuis Brussel, Belgium. We used individual data for pain intensity reporting from the prospective, multicentre, cross‐sectional INTERVAL study [15]. The main aim of the INTERVAL study was to explore the association between heart rate variability and pain intensity measures in patients with chronic pain, and written informed consent was obtained for each participant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis on cerebrospinal fluid indicated a modulation of a wide variety of proteins which could be categorized under neuroprotection, synaptic plasticity, nociceptive signaling and immune regulation [59,60]. Alterations were revealed when exploring the effect of neuromodulation on heart rate variability [61], however, when evaluating whether this measure could serve as a surrogate marker for pain intensity at the individual level, negative results were reported [62]. Presumably, some of the more objective outcome measurements hold the capacity to measure the actual ability of the effect of a pain management treatment.…”
Section: Potential Points Of Improvements For a Holistic Approachmentioning
confidence: 99%